2022
DOI: 10.1590/s1678-3921.pab2022.v57.02312
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of pitaya by indirect organogenesis evaluated by scanning electron microscopy and flow cytometry

Abstract: The objective of this work was to evaluate the induction of indirect organogenesis by concentrations of dichlorophenoxyacetic acid (2,4-D) and thidiazuron (TDZ) in pitaya (Hylocereus undatus) explants, using scanning electron microscopy and the flow cytometry technique. The treatments consisted of the concentrations of 0, 2.0, and 4.0 mg L-1 2,4-D and TDZ and of the combinations of these regulators. Percentages of callus coverage at 45 and 60 days were evaluated. The explants subjected to the treatments were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Fan et al [ 191 ] used 442 inter-simple sequence repeat (ISSR) markers, producing 55 primers exhibiting no polymorphism and somaclonal variation after 15 multiplication cycles of shoots; the results were attributed to the existence of high genetic fidelity in H. undatus . Hua et al [ 190 ] and Rodrigues et al [ 200 ] also reported no somaclonal variation after multiple in vitro cycles.…”
Section: Breeding Through Biotechnologymentioning
confidence: 99%
“…Fan et al [ 191 ] used 442 inter-simple sequence repeat (ISSR) markers, producing 55 primers exhibiting no polymorphism and somaclonal variation after 15 multiplication cycles of shoots; the results were attributed to the existence of high genetic fidelity in H. undatus . Hua et al [ 190 ] and Rodrigues et al [ 200 ] also reported no somaclonal variation after multiple in vitro cycles.…”
Section: Breeding Through Biotechnologymentioning
confidence: 99%